Learning well, living well: the causal effects of higher education on self-rated health and mental health in China - Yang, Shudong (Frontiers in Public Health, 2025)
BackgroundIn the context of rapid population aging and the global health challenges posed by the COVID-19 pandemic, understanding the social determinants of health has become increasingly important. Education, as a key socioeconomic factor, plays a critical role in shaping individual health outcomes. However, empirical evidence on the causal relationship between higher education (HE) and health, particularly in developing countries like China, remains limited.MethodsUtilizing data from the 2022 China Family Panel Studies (CFPS), this study primarily employed Ordinary Least Squares (OLS) regression to estimate the effects of HE on self-rated health (SRH) and mental health (MH). To address potential endogeneity and strengthen causal inference, an instrumental variable (IV) approach was implemented. Robustness tests included substituting explanatory variables, excluding specific samples, and employing an ordered Probit model. Mechanism analysis explored the roles of health behaviors, household income, and social capital. Intergenerational effects of parental HE on children’s health were also examined.ResultsHigher education was found to have a statistically significant positive impact on both SRH and MH (p < 0.01). These results remained consistent across all robustness tests and when using the IV approach, supporting a causal interpretation. Mediation analysis revealed that HE improves health by fostering healthier behaviors, increasing household income, and enhancing social capital. Furthermore, paternal HE significantly improved children’s SRH (p < 0.05), while maternal HE significantly enhanced children’s MH (p < 0.01).ConclusionThis study provides robust evidence that higher education serves as a crucial determinant of health in China, with beneficial effects extending across generations. The findings highlight the potential of educational interventions as a strategic avenue for improving public health and reducing health disparities.